Implementasi Program Pendidikan Magrib Mengaji Di Tpa An-Nur Jorong Ulu Simpang Kecamatan Koto Balingka - Riski, Rina; Hasibuan, Hendra; Nisa, Yarotun; Pulungan, Tria Arzeta; Nasution, Ajijah Rahma; Baik, Muhammad; Husna, Asmaul; Safitri, Heni; Simamora, Fadilatun Nikmah (Penerbit Widina, Widina Media Utama, 2024)
Maghrib reciting the Quran is an activity carried out by a person or group in a non-formal place which is carried out after the evening prayer. The Maghrib Quran recitation program aims to educate children in understanding and memorizing the Quran, while at the same time instilling Islamic religious values. Maghrib reciting the Quran also functions as a means to strengthen community ties and build time discipline and discipline in worship. It is not only teachers who play an important role in teaching their children, but parents also have an important role in understanding religious knowledge so that later a child will have in-depth knowledge of the world and the afterlife.ABSTRAKMaghrib mengaji adalah kegiatan yang dilakukan seseorang atau sekelompok di suatu tempat non formal yang kegiatannya dilaksanakan sehabis salat magrib. Program magrib mengaji bertujuan untuk mendidik anak-anak dalam memahami dan menghafal alquran, sekaligus menanamkan nilai-nilai agama islam. Magrib mengaji juga berfungsi sebagai sarana untuk memperkuat ikatan komunitas dan membangun disiplin waktu serta kedisiplinan dalam beribadah. Bukan hanya guru yang berperan penting dalam mengajari anaknya tetapi orang tua juga memiliki peranan penting dalam pemahaman ilmu agama agar nantinya seorang anak tersebut memiliki pengetahuan mendalam akan dunia dan akhirat.